An introduction to thermogeology : ground source heating and cooling - Banks, David, 1961- (Chichester, West Sussex ; Somerset, N.J. : Wiley-Blackwell, 2012)
"This authoritative guide provides a basis for understanding the emerging technology of ground source heating and cooling. It equips engineers, geologists, architects, planners and regulators with the fundamental skills needed to manipulate the ground's huge capacity to store, supply and receive heat, and to implement technologies (such as heat pumps) to exploit that capacity for space heating and cooling. The author has geared the book towards understanding ground source heating and cooling from the ground side (the geological aspects), rather than solely the building aspects. He explains the science behind thermogeology and offers practical guidance on different design options. An Introduction to Thermogeology: ground source heating and cooling is aimed primarily at professionals whose skill areas impinge on the emerging technology of ground source heating and cooling. They will be aware of the importance of the technology and wish to rapidly acquire fundamental theoretical understanding and design skills. This second edition has been thoroughly updated and expanded to cover new technical developments and now includes end-of-chapter study questions to test the reader's understanding."--
5.6: Ground source heat: a competitor in energy markets?6: Ground Source Cooling; 6.1: Our cooling needs in space; 6.2: Scale effects and our cooling needs in time; 6.3: Traditional cooling; 6.4: Dry coolers; 6.5: Evaporation; 6.6: Chillers/heat pumps; 6.7: Absorption heat pumps; 6.8: Delivery of cooling in large buildings; 6.9: Dehumidification; 6.10: Passive cooling using the ground; 6.11: Active ground source cooling; 6.12: An example of open-loop groundwater cooling; 7: Options and Applications for Ground Source Heat Pumps; 7.1: How much heat do I need?; 7.2: Sizing a GSHP.
Includes bibliographical references and index.
Print version record.
Keywords: Ground source heat pump systems; TECHNOLOGY & ENGINEERING -- Construction -- Heating, Ventilation & Air Conditioning; Ground source heat pump systems; Electronic books